Anthracycline-Associated T1 Mapping Characteristics Are Elevated Independent of the Presence of Cardiovascular Comorbidities in Cancer Survivors. (August 2016) - Jordan, Jennifer H.; Vasu, Sujethra; Morgan, Timothy M.; D'Agostino, Ralph B.; Meléndez, Giselle C.; Hamilton, Craig A.; Arai, Andrew E.; Liu, Songtao; Liu, Chia-Ying; Lima, João A.C.; Bluemke, David A.; Burke, Gregory L.; et al.
Abstract : Background—: Cardiovascular magnetic resonance T1 mapping characteristics are elevated in adult cancer survivors; however, it remains unknown whether these elevations are related to age or presence of coincident cardiovascular comorbidities. Methods and Results—: We performed blinded cardiovascular magnetic resonance analyses of left ventricular T1 and extracellular volume (ECV) fraction in 327 individuals (65% women, aged 64±12 years). Thirty-seven individuals had breast cancer or a hematologic malignancy but had not yet initiated their treatment, and 54 cancer survivors who received either anthracycline-based (n=37) or nonanthracycline-based (n=17) chemotherapy 2.8±1.3 years earlier were compared with 236 cancer-free participants. Multivariable analyses were performed to determine the association between T1/ECV measures and variables associated with myocardial fibrosis. Age-adjusted native T1 was elevated pre- (1058±7 ms) and post- (1040±7 ms) receipt of anthracycline chemotherapy versus comparators (965±3 ms; P <0.0001 for both). Age-adjusted ECV, a marker of myocardial fibrosis, was elevated in anthracycline-treated cancer participants (30.4±0.7%) compared with either pretreatment cancer (27.8±0.7%; P <0.01) or cancer-free comparators (26.9±0.2%; P <0.0001). T1 and ECV of nonanthracycline survivors were no different than pretreatment survivors ( P =0.17 and P =0.16, respectively). Native T1 and ECV remained elevated in cancer survivors after accounting for demographics (including age), myocardial fibrosis risk factors, and left ventricular ejection fraction or myocardial mass index ( P <0.0001 for all). Conclusions—: Three years after anthracycline-based chemotherapy, elevations in myocardial T1 and ECV occur independent of underlying cancer or cardiovascular comorbidities, suggesting that imaging biomarkers of interstitial fibrosis in cancer survivors are related to prior receipt of a potentially cardiotoxic cancer treatment regimen. Abstract : Supplemental Digital Content is available in the text.